(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Preservation and strengthening of the health of children and adolescents, formation of healthy lifestyle skills in them is the main task of the state and the education system. One of the components of a healthy lifestyle for schoolchildren is the optimal level of physical activity. The modern educational process in educational institutions often leads to a deterioration in the health of children and adolescents. The transition of children of different ages to distance learning technologies, according to experts, can cause adverse changes in the functional state due to a low motor component and significant mental stress. Such a situation requires improving the rational organization of the motor activity of children and adolescents during distance learning. The purpose of our study is to develop conceptual mechanisms that influence the level of motor activity of schoolchildren in the process of online learning. Research methods - analysis and generalization of literary sources, questionnaires, comparative analysis, generalization. Our study used a questionnaire method to identify the main conceptual mechanisms influencing the level of physical activity of children and adolescents in the context of online learning, including organizational, psychological, social and technological. Research results: The level of physical activity of schoolchildren in the process of online learning is insufficient, which creates risks for their physical and mental health. The questionnaire identified key problems, including lack of motivation, insufficient integration of physical exercise into the educational process and low awareness of the possibilities of digital platforms for training. To increase the physical activity of children and young people, it is recommended to: develop active break programs that can be integrated into the schedule of online classes; raise awareness of students and parents about the benefits of physical activity; stimulate the use of mobile applications for physical exercise through incentives and interactive challenges; integrate elements of movement into the educational process, for example, through game-based classes.